Iron-based alloy with high corrosion and wear resistance

By using iron-based alloys, corrosion-resistant matrix and hard phase are formed, the high loss and corrosion problems of gray cast iron brake disc materials are solved, and higher wear resistance and corrosion resistance are achieved, and braking performance and aesthetics are improved. sex.

CN114787395BActive Publication Date: 2025-02-25OERLIKON METCO (USA) CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202080083745.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-18
Filing Date
2020-12-01
Publication Date
2025-02-25
Estimated Expiration
2040-12-01

AI Technical Summary

Technical Problem

The existing gray cast iron brake disc materials have high material loss and corrosion problems during operation, resulting in increased particle emissions, reduced aesthetics and poor braking performance.

Method used

The iron-based alloy is used to form a corrosion-resistant matrix and a hard phase with a high volume/mole fraction in situ, limiting the amount of cobalt and nickel incorporated, and improving the wear and corrosion resistance of the alloy.

Benefits of technology

It significantly reduces corrosion and wear of materials, reduces particle emissions, improves the aesthetics and braking performance of the brake discs, while maintaining a similar cost advantage to gray cast iron.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114787395B_ABST
    Figure CN114787395B_ABST
Patent Text Reader

Abstract

Example embodiments relate to alloys having high corrosion resistance and high wear resistance. Specifically, example embodiments relate to an iron-based alloy comprising: 20 wt % to 50 wt % Cr; 0 wt % to 15 wt % Mo; 0 wt % to 15 wt % W; 3 wt % to 6 wt % B; and the balance of iron and impurities. In example embodiments, under substantially balanced solidification conditions, at 1300 K, the pitting resistance equivalent number (PREN) is greater than 30. In example embodiments, under substantially balanced solidification conditions, at 1300 K, the mole fraction of the hard phase of the alloy is between 45% and 80%. Under substantially balanced solidification conditions, the liquidus of the alloy may be less than 2000K.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This international application claims the benefit of U.S. Provisional Application No. 62 / 949,761, filed on December 18, 2019, the disclosure of which is expressly incorporated herein by reference in its entirety. Technical Field

[0003] The present technology generally relates to alloys having high corrosion resistance and high wear resistance. In particular, example embodiments relate to iron-based alloys for automotive disc brakes. Background Art

[0004] Gray cast iron is currently the standard material used for brake discs in many transportation options, such as cars and trucks. It is a good choice due to its low cost, easy manufacturability through casting, and acceptable mechanical properties. However, gray cast iron has some problematic properties, including low wear resistance that leads to high material loss during operation and low corrosion resistance that leads to corrosion during normal operation. Combined with regulatory pressure, there is an increasing demand for brake disc material solutions that maintain the attractive properties of cast iron, but reduce the corrosion and wear problems faced by the material in the field. Due to high costs, alternative technologies such as composite brake discs are often unattractive for large-scale production. Generally, two major factors drive this market trend. The first factor is the increased pressure from regulatory agencies to reduce fine particle emissions due to brake disc wear, and the second factor is the reduction in the use of friction brakes in vehicles capable of regenerative braking, which leads to corrosion of cast iron brakes. Visible corrosion (rust) is an aesthetic issue, but it may also reduce braking effectiveness.

[0005] Furthermore, in many coating applications there is strong regulatory and safety pressure to reduce or eliminate the use of nickel and / or cobalt. Both materials are commonly used as the metallic phase in thermal spray and other coatings. Summary of the invention

[0006] In example embodiments, alloys and coatings provide improved brake disc performance by increasing the wear and corrosion resistance of the disc. This can result in reduced particulate emissions, improved disc aesthetics, and / or improved braking performance compared to standard materials (e.g., gray cast iron). In addition, because the alloys of example embodiments are iron-based, they can be provided and used at a competitive cost compared to more expensive metals and / or composite materials.

[0007] Alloys according to example embodiments are iron-based and may limit the amount of cobalt and nickel incorporated, thus increasing their attractiveness for many wear and corrosion applications.

[0008] Example embodiments include iron-based alloys with high corrosion resistance and wear resistance by in-situ formation of corrosion-resistant matrix and high volume / mole fraction of hard phase. In example embodiments, borides constitute hard phases, which is beneficial from a design point of view, because boron has a relatively low solid solution solubility with iron and iron alloys, which drives the precipitation of boride phases even at the rapid cooling rate inherent in thermal spraying and / or powder atomization. With the formation of these beneficial phases, harmful phases that may reduce the toughness and ductility of the alloy, including intermetallic phases, such as σ phases or Laves phases, can be reduced or eliminated. In example embodiments, due to the element balance in the alloy, the alloy may reduce the fraction of intermetallic phases, and the reduction of harmful intermetallic phases can also be driven thermodynamically by the free energy of each phase formed during solidification. In example embodiments, the manufacturability of the alloy by atomization can be achieved by controlling the liquidus temperature of the alloy.

[0009] In an example embodiment, the iron-based alloy includes 20 wt % to 50 wt % Cr, 0 wt % to 15 wt % W, 0 wt % to 15 wt % Mo, and 3 wt % to 6 wt % B. In an example embodiment, under substantially balanced solidification conditions, at 1300 K, the pitting resistance equivalent number (PREN) calculated as Cr+3.3*(Mo+0.5*W)+16*N is greater than 30. In an example embodiment, under substantially balanced solidification conditions, at 1300 K, the mole fraction of the hard phase of the alloy is between 40% and 80%. In an example embodiment, if the mole fraction of the hard phase of the alloy is greater than 80%, the excessive fraction of intermetallic phases and / or borides may result in embrittlement and poor mechanical properties, as well as reduced toughness and ductility. In an example embodiment, a mole fraction of the hard phase of the alloy less than 45% results in reduced wear performance.

[0010] In example embodiments, the liquidus of the alloy is less than 2000K under substantially balanced solidification conditions. In example embodiments, if the liquidus is greater than 2000K, the manufacturability of the material by atomization is reduced, which will make the process expensive and reduce production yields. In example embodiments, if the concentration of Cr is greater than 50 wt%, Laves phases may form, resulting in low PREN and low corrosion resistance. In example embodiments, if the concentration of W or Mo is greater than 15 wt%, Laves phases may form, resulting in high cost and low pitting resistance. In example embodiments, if the concentration of B is greater than 6 wt%, excessive hard phases may form, resulting in low wear performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In the following detailed description, the present disclosure is further described by way of non-limiting examples of preferred embodiments of the present disclosure, with reference to the several drawings wherein like characters represent like elements throughout the several views of the drawings.

[0012] Figure 1 is a graph illustrating thermodynamic solidification of alloy (X4) according to example embodiments.

[0013] Figure 2 is a graph illustrating thermodynamic solidification of an alloy (X5) according to an example embodiment.

[0014] Figure 3 is an illustration of the microstructure of a quenched arc-melted ingot of X4 according to an example embodiment.

[0015] Figure 4 is an illustration of the microstructure of a quenched arc-melted ingot of X5 according to an example embodiment.

[0016] Figure 5 is a graph illustrating thermodynamic solidification of an alloy (X9) according to an example embodiment. DETAILED DESCRIPTION

[0017] By one or more of the various aspects, embodiments, and / or specific features or subassemblies of the present disclosure, it is intended to provide one or more advantages as specifically described above and pointed out below.

[0018] Thermodynamics

[0019] In example embodiments of the present disclosure, the alloys may be adequately described by equilibrium or near-equilibrium thermodynamic parameters, such as Figure 1 and 2 One way to predict the corrosion performance of ferrous alloys is to use PREN calculated according to the following equation (1):

[0020] PREN = Cr+3.3 * (Mo+0.5 * W)+16 * N (1),

[0021] The element values ​​are expressed as weight percentage.

[0022] In single-phase materials, such as most ferritic stainless steels, PREN is applied to the bulk alloy composition. However, because the alloys in the present disclosure may include multiple phases, PREN values ​​are calculated based on the equilibrium thermodynamic conditions of the matrix phase, without considering the composition of other phases (e.g., borides) that may form. The matrix phase is defined as a face-centered cubic (FCC) or body-centered cubic (BCC) iron-rich metallic phase. Therefore, the matrix PREN value can be used to accurately predict the relative corrosion performance of multiphase materials. In example embodiments of the present disclosure, the matrix phase is BCC ferrite.

[0023] Figure 1 is a diagram illustrating the thermodynamic solidification of alloy (X4) according to an example embodiment. Figure 1 In , the X-axis represents temperature, and the Y-axis represents mole fraction. Figure 1 As described in, based on the chemistry of the BCC phase (the BCC phase is the only matrix phase present under equilibrium solidification conditions), at 1300 K, the matrix PREN of alloy X4 is calculated to be 32.5, based on the calculated Cr content of 21.2 wt.%, Mo content of 1.9%, and W content of 3.0 wt.%, as represented by reference numeral 101; and at 1000 K, the matrix PREN of alloy X4 is calculated to be 20.0, based on the Cr content of 16.9 wt.%, Mo content of 0.46 wt.%, and W content of 0.98 wt.%, as represented by reference numeral 102.

[0024] Figure 2 is a diagram illustrating the thermodynamic solidification of alloy (X5) according to an example embodiment. Figure 2 In , the X-axis represents temperature, and the Y-axis represents mole fraction. Figure 2 In the embodiment of the present invention, at 1300 K, the matrix PREN of alloy X5 is calculated to be 42.7, based on a calculated Cr content of 31.2 wt. %, a Mo content of 2.0 wt. %, and a W content of 3.0 wt. %, as represented by reference numeral 201; and at 1000 K, the matrix PREN of alloy X5 is calculated to be 25.0, as represented by reference numeral 202, including a calculated Cr content of 21.9 wt. %, a Mo content of 0.56 wt. %, and a W content of 0.78 wt. %, based on the chemistry of the BCC phase.

[0025] Figure 5 is a diagram illustrating the thermodynamic solidification of an alloy (X9) according to an example embodiment. Figure 5 In , the X-axis represents temperature, and the Y-axis represents mole fraction. Figure 5 In the embodiment of the present invention, at 1300 K, the matrix PREN of alloy X9 is calculated to be 35.7, based on the calculated Cr content of 30.1 wt. % and the W content of 3.4 wt. %, as indicated by reference 501; and at 1000 K, the matrix PREN of alloy X9 is calculated to be 27.0, with the calculated Cr content of 24.6 wt. % and the W content of 1.5 wt. %, as indicated by reference 502, based on the chemistry of the BCC phase.

[0026] Table 1 below provides a list of alloys produced by arc melting and their nominal chemistries in weight percent.

[0027] Table 1 - Nominal concentrations of alloys produced by arc melting

[0028] B Cr Fe Mo W P130-X1 4.5 40 margin 2 0 P130-X2 5.1 34 margin 10 2 P130-X3 4.5 38 margin 4 2 P130-X4 5.3 32 margin 10 4 P130-X5 4.5 42 margin 4 2 P130-X6 4.5 44 margin 4 2 P130-X7 4.4 41 margin 0 2 P130-X9 3.7 40 margin 0 2

[0029] In example embodiments of the present disclosure, at 1300 K, the matrix PREN is greater than 30 (0.30 on the Y axis). In other example embodiments of the present disclosure, at 1300 K, the matrix PREN is greater than 32 (0.32 on the Y axis). In other example embodiments of the present disclosure, at 1300 K, the matrix PREN is greater than 34 (0.34 on the Y axis). In further example embodiments of the present disclosure, at 1300 K, the matrix PREN is greater than 38 (0.38 on the Y axis). In still other example embodiments of the present disclosure, at 1300 K, the matrix PREN is greater than 40 (0.40 on the Y axis).

[0030] In addition, in example embodiments of the present disclosure, at 1000K, the matrix PREN is greater than 15 (0.15 on the Y axis). In further example embodiments of the present disclosure, at 1000K, the matrix PREN is greater than 17 (0.17 on the Y axis). In still further example embodiments of the present disclosure, at 1000K, the matrix PREN is greater than 19 (0.19 on the Y axis). In example embodiments of the present disclosure, at 1000K, the matrix PREN is greater than 20 (0.20 on the Y axis).

[0031] Another way to predict the corrosion performance of ferrous alloys is by measuring the chromium content of the alloy. In an example embodiment, the chromium content of the matrix phase is calculated under equilibrium solidification conditions. Table 2 below also lists the alloys produced and their matrix chromium content calculated under equilibrium solidification conditions.

[0032] In example embodiments, at 1300 K, the matrix comprises greater than 16% chromium by weight. In other example embodiments, at 1300 K, the matrix comprises greater than 18% chromium by weight. In further example embodiments, at 1300 K, the matrix comprises greater than 20% chromium by weight. In still further example embodiments, at 1300 K, the matrix comprises greater than 22% chromium by weight. In still further example embodiments, at 1300 K, the matrix comprises greater than 24% chromium by weight. In still further example embodiments, at 1300 K, the matrix comprises greater than 26% chromium by weight. In still further example embodiments, at 1300 K, the matrix comprises greater than 28% chromium by weight.

[0033] Chromium contributes to corrosion resistance in high chloride environments; however, the presence of molybdenum and tungsten also improves the pitting resistance of ferrous alloys in high chloride environments where Cr is also present. Table 2 below also lists the alloys produced and their calculated matrix molybdenum + tungsten content under equilibrium solidification conditions.

[0034] In example embodiments, the matrix comprises greater than 0.5% by weight of molybdenum and tungsten combined at 1300 K. In example embodiments, the matrix comprises greater than 1% by weight of molybdenum and tungsten combined at 1300 K. In example embodiments, the matrix comprises greater than 2% by weight of molybdenum and tungsten combined at 1300 K. In other example embodiments, the matrix comprises greater than 4% by weight of molybdenum and tungsten combined at 1300 K.

[0035] The formation of intermetallic phases in high Cr, Mo and / or W stainless steels is a problem with high fractions of intermetallic phases associated with reduced toughness and / or ductility. Since such materials tend to have reduced to no cracking after being deposited by thermal spraying or other methods, it is advantageous to reduce the presence of any embrittled phases. In example embodiments, the intermetallic phase mole fraction is defined as the sum of all χ, σ and Laves phases under equilibrium solidification conditions. In some applications, such as brake discs, during extreme braking events, surface temperatures can reach 800K, and therefore it is advantageous that the intermetallic phases do not precipitate during use.

[0036] exist Figure 1 In the alloy X4 described in , at 800K, the only intermetallic phase present is the Laves phase represented by reference numeral 103, so the molar fraction of the intermetallic phase at 800K is calculated to be 6.4%. Figure 2 In the alloy X5 described in , at 800K, both the Laves phase represented by reference numeral 203 and the σ phase represented by reference numeral 204 exist, so the total calculated molar fraction is calculated to be 13.0%. Figure 5 In the alloy X9 described in , at 800 K, both the Laves phase represented by reference numeral 503 and the χ phase represented by reference numeral 504 are present, so the total calculated mole fraction is 13.5%.

[0037] In example embodiments, the alloy comprises less than 20% by mole percent intermetallic phase at 800 K. In other example embodiments, the alloy comprises less than 15% by mole percent intermetallic phase at 800 K. In further example embodiments, the alloy comprises less than 10% by mole percent intermetallic phase at 800 K. In still further example embodiments, the alloy comprises less than 8% by mole percent intermetallic phase at 800 K.

[0038] The formation of hard phases (e.g., borides, carbides, borocarbides, oxides, and nitrides) can improve the wear resistance of the alloy. There are practical limits to the fraction of hard phases, where too high a value may cause the alloy to crack after deposition or in use, especially when exposed to periodic and rapid changes in temperature. The hard phases in the present disclosure can be calculated as the sum of all borides, carbides, borocarbides, oxides, and / or nitrides under equilibrium solidification conditions.

[0039] exist Figure 1 In the alloy X4 described in , at 1300 K, there are two hard phases: an M3B2 phase represented by reference numeral 104 and an M2B phase represented by reference numeral 105; the total amount of these hard phases is 66.7 mol%. Figure 2 In the alloy X5 described in , there is only one hard phase: the M2B phase indicated by reference numeral 205, so at 1300 K, the molar fraction of the hard phase is 58.8%. Figure 5 In the alloy X9 described in , there is only one hard phase: the M2B phase represented by reference numeral 505, and therefore, at 1300 K, the molar fraction of the hard phase is 49%.

[0040] In example embodiments, under equilibrium or near equilibrium solidification conditions, the mole fraction of the hard phase is between 45% and 80%. In other example embodiments of the present disclosure, the mole fraction of the hard phase is between 50% and 75%. In further example embodiments of the present disclosure, the mole fraction of the hard phase is between 50% and 60%. In further example embodiments of the present disclosure, the mole fraction of the hard phase is between 55% and 70%. In example embodiments, under equilibrium or near equilibrium solidification conditions, the mole fraction of the hard phase is between 35% and 65%. In other example embodiments of the present disclosure, the mole fraction of the hard phase is between 40% and 60%. In further example embodiments of the present disclosure, the mole fraction of the hard phase is between 45% and 55%.

[0041] Forming a high temperature phase during melting and atomization can reduce the manufacturability of the alloy by limiting fluidity. Limited fluidity may require special equipment to melt, may reduce the productivity of atomization, and / or make it impossible to produce on an industrial scale. In order to ensure higher fluidity, the liquidus temperature under equilibrium solidification conditions is controlled because the lower liquidus temperature is related to the fluidity increased during atomization. In example embodiments, fluidity and liquidus temperature can be inversely correlated.

[0042] The liquidus temperature is thermodynamically defined as the lowest temperature at which an alloy is 100% liquid. In alloys X4 and X5, the liquidus temperature is 1925K, as indicated by reference numerals 106 and 206. In alloy X9, the liquidus temperature is 1819K.

[0043] In example embodiments, the liquidus temperature of the alloy is less than 2000 K. In other example embodiments, the liquidus temperature of the alloy is less than 1975 K. In further example embodiments, the liquidus temperature of the alloy is less than 1950 K. In still further example embodiments, the liquidus temperature of the alloy is less than 1925 K. In still further example embodiments, the liquidus temperature of the alloy is less than 1900 K. In still further example embodiments, the liquidus temperature of the alloy is less than 1875 K. In still further example embodiments, the liquidus temperature of the alloy is less than 1850 K.

[0044] The matrix phase structure can determine the suitability of the material for brake discs and other applications. In some embodiments, the alloys of the present disclosure may have Figure 1 , 2 and 5, a ferrite matrix represented as BCC_A2. In some embodiments, the only matrix phase is BCC_A2 without an iron FCC iron phase. In some embodiments, the fraction of the FCC iron matrix phase is less than 5 mol% at any temperature. In some embodiments, the fraction of the FCC iron matrix phase is less than 10 mol% at any temperature. In some embodiments, the fraction of the FCC iron matrix phase is less than 20 mol% at any temperature. In some embodiments, the fraction of the FCC iron matrix phase is less than 25 mol% at any temperature.

[0045] In some embodiments, it is preferred that the hard phase is entirely or predominantly chromium boride. This is advantageous because the chromium content contributes to good corrosion performance. Chromium boride also forms at lower temperatures than many other hard phases (e.g., MC carbides and borides of molybdenum and tungsten). The mole fraction of chromium boride is defined as the fraction of M2B at 1300K, where M2B contains greater than 90% Fe+Cr+B.

[0046] exist Figure 5 In the alloy X9 shown in FIG, the chromium boride fraction is 49 mol %.

[0047] In some embodiments of the present disclosure, the mole fraction of chromium boride is between 40-65 mol %. In some embodiments of the present disclosure, the mole fraction of chromium boride is between 45-55 mol %. In some embodiments of the present disclosure, the mole fraction of chromium boride is between 45-70 mol %. In some embodiments of the present disclosure, the mole fraction of chromium boride is between 55-70 mol %.

[0048] In some embodiments, it is important that the hard phase is formed primarily as a hypereutectic phase. This ensures that the hard phase is sufficiently coarse after being atomized or otherwise made into a powder. A hard phase that is too fine may not provide the desired abrasive and / or wear properties required for a given application. The hypereutectic hard phase fraction is measured as the sum of all hard phases at the lowest temperature at which the matrix has not yet solidified. Figure 5 For alloy X9, this occurs at 1600 K. Therefore, the hypereutectic hard phase fraction in X9 is 31.7 mol %, as Figure 5 As shown in the mark 507.

[0049] In some embodiments, the hypereutectic hard phase fraction is greater than 25%. In some embodiments, the hypereutectic hard phase fraction is greater than 28%. In some embodiments, the hypereutectic hard phase fraction is greater than 30%.

[0050] Microstructure

[0051] In example embodiments, alloys can also be described by their microstructural features. Forming hard phases (e.g., borides, carbides, borocarbides, oxides, and nitrides) can improve the wear resistance of alloys. There are practical limitations for the fraction of hard phases, where too high values ​​may cause the alloy to crack after deposition or in use, especially when exposed to periodic and rapid changes in temperature. Hard phases in the present disclosure can be calculated as the sum of all borides, carbides, borocarbides, oxides, and nitrides, as measured on the sample of the arc melting of the alloy using quantitative metallographic techniques.

[0052] exist Figure 3 In the microstructure of alloy X4 described in , the volume fraction of the hard phase was measured to be 67%, which is the sum of the iron-chromium boride represented by reference numeral 301 and the iron-chromium-molybdenum-tungsten boride represented by reference numeral 302. Figure 4 In the microstructure of alloy X5 described in , the volume fraction of the hard phase was measured to be 57%, which is the sum of the iron-chromium borides represented by the reference 401.

[0053] The PREN of the matrix phase is a strong predictor of the corrosion performance of the alloy. As discussed above with respect to equation (1), the PREN is calculated as [Cr+3.3*(Mo+0.5*W)+16*N], where the element values ​​are in weight percent. The element weight percents are measured using energy dispersive X-ray spectroscopy (EDS) in a scanning electron microscope (SEM).

[0054] exist Figure 3 In the microstructure of alloy X4 illustrated in , PREN calculated from the matrix phase represented by reference numeral 303, measured by EDS, is equal to 38.3. Figure 4In the microstructure of alloy X5 illustrated in FIG. 5 , the PREN of the matrix phase, represented by reference numeral 402, was measured to be equal to 48.3. The measured matrix PREN values ​​for all produced arc-melted alloys are listed in Table 2.

[0055] Table 2 - Thermodynamic and empirical results for arc-melted alloys

[0056]

[0057] In some applications, the alloys described in the present disclosure can be deposited as coatings intended to provide corrosion resistance. In the presence of corrosive media (e.g., water with a high chloride content), excessive coating porosity may allow the corrosive media to penetrate into the substrate. If such penetration occurs, corrosion of the substrate may result in surface discoloration, reduced coverage, and / or peeling of the coating from the substrate. As a result, it may be advantageous to control the percentage of porosity in a coating deposited by thermal spraying or other deposition methods.

[0058] Table 3 below summarizes alloys of the present disclosure that have been sprayed by HVOF at 3 parameters, and their resulting porosity as measured by ASTM E2109-01.

[0059] In example embodiments, the porosity of the coating formed from the alloy may be less than 3%. In other example embodiments of the present disclosure, the porosity of the coating formed from the alloy may be less than 2%. In further example embodiments of the present disclosure, the porosity of the coating formed from the alloy may be less than 1.5%. In still further example embodiments of the present disclosure, the porosity of the coating formed from the alloy may be less than 1%.

[0060] A predictor of coating wear performance can be the hardness measured by the Vickers test method at 0.3 kgf (HV0.3). On the other hand, too much hardness may indicate low toughness and / or ductility, which may lead to cracking or peeling in use. Hardness is generally inversely correlated with toughness or ductility. Table 3 below summarizes the HV0.3 values ​​of three HVOF sprayed alloys of the present disclosure.

[0061] In example embodiments, the Vickers hardness HV0.3 is between 500-1050. In example embodiments, the HV0.3 is between 600-950.

[0062] Table 3 - Results of HVOF sprayed powders

[0063]

[0064] Chemical

[0065] In example embodiments of the present disclosure, the alloy can be described by its bulk chemistry. In other example embodiments, the powder comprises, by weight percentage: 20% to 50% chromium, 0% to 15% molybdenum, 0% to 15% tungsten, 3% to 6% boron. In further example embodiments, the powder comprises, by weight percentage: 25% to 50% chromium, 0% to 15% molybdenum, 0% to 15% tungsten, 3% to 6% boron. In still further example embodiments, the powder comprises, by weight percentage: 30% to 45% chromium, 0% to 15% molybdenum, 0% to 15% tungsten, 3% to 6% boron. In still further example embodiments, the powder comprises, by weight percentage: 20% to 50% chromium, 0% to 15% molybdenum, 0% to 15% tungsten, 3.3% to 5.5% boron. In other example embodiments, the powder comprises, by weight percentage: 20% to 50% chromium, 0% to 15% molybdenum, 0% to 15% tungsten, 3.3% to 5.5% boron. It should be understood that in the above embodiments, the balance of alloying elements includes iron and impurities.

[0066] In an example embodiment, the powder comprises, by weight percentage: 28% to 36% chromium, 8% to 12% molybdenum, 2% to 6% tungsten, 4.8% to 5.6% boron, the balance iron and impurities. In other example embodiments, the powder comprises, by weight percentage: 25% to 39% chromium, 7% to 13% molybdenum, 2% to 6% tungsten, 4.6% to 5.8% boron. It should be understood that in the above embodiments, the balance of alloying elements includes iron and impurities.

[0067] In an example embodiment, the powder comprises, by weight percentage: 38% to 46% chromium, 3% to 6% molybdenum, 0% to 4% tungsten, 4.0% to 4.8% boron, the balance iron and impurities. In other example embodiments, the powder comprises, by weight percentage: 36% to 48% chromium, 2% to 8% molybdenum, 0% to 6% tungsten, 3.8% to 5.0% boron. It should be understood that in the above embodiments, the balance of alloying elements includes iron and impurities.

[0068] In an example embodiment, the powder comprises, by weight percentage, 36% to 48% chromium, 0% to 4% tungsten, 3.8% to 4.8% boron, and the balance comprises iron and impurities.

[0069] In an example embodiment, the powder comprises, by weight percentage, 35% to 45% chromium, 0% to 4% tungsten, 3.4% to 4.2% boron, and the balance comprises iron and impurities.

[0070] In an example embodiment, the powder comprises, by weight percentage: 35% to 45% chromium, 0% to 4% molybdenum + tungsten, 3.4% to 4.2% boron, the balance comprising iron and impurities.

[0071] In an example embodiment, the powder comprises, by weight percentage: 35% to 45% chromium, 0% to 8% molybdenum + tungsten, 3.4% to 4.2% boron, the balance comprising iron and impurities.

[0072] In an example embodiment, the powder comprises, by weight percentage: 35% to 45% chromium, 0.5% to 4% molybdenum + tungsten, 3.4% to 4.2% boron, the balance comprising iron and impurities.

[0073] In an example embodiment, the powder comprises, by weight percentage: 35% to 45% chromium, 3.4% to 4.2% boron.

[0074] In example embodiments, the powder contains less than 1% carbon by weight. In other example embodiments, the powder contains less than 0.5% carbon by weight. In further example embodiments, the powder contains less than 0.25% carbon by weight. In still further example embodiments, the powder contains less than 0.1% carbon by weight.

[0075] Due to regulatory, environmental and safety concerns, it may be desirable to limit nickel and / or copper in all wear surfaces, as excessive nickel concentrations lead to reduced ferrite stability and increased environmental risks.Example embodiments of the present disclosure specifically limit the nickel content of the feedstock powder.

[0076] In example embodiments, the powders and coatings produced contain less than 5% nickel by weight. In other example embodiments, the powders and coatings produced contain less than 2% nickel by weight. In further example embodiments, the powders and coatings produced contain less than 1% nickel by weight. In still further example embodiments, the powders and coatings produced contain less than 0.5% nickel by weight. In still further example embodiments, the powders and coatings produced contain less than 0.2% nickel by weight. In other example embodiments, the powders and coatings produced contain less than 0.15% nickel by weight. In still further example embodiments, the powders and coatings produced contain less than 0.1% nickel by weight.

[0077] In example embodiments, the powders and coatings produced contain less than 5% copper by weight. In other example embodiments, the powders and coatings produced contain less than 2% copper by weight. In further example embodiments, the powders and coatings produced contain less than 1% copper by weight. In still further example embodiments, the powders and coatings produced contain less than 0.5% copper by weight. In still further example embodiments, the powders and coatings produced contain less than 0.2% copper by weight. In other example embodiments, the powders and coatings produced contain less than 0.15% copper by weight. In still further example embodiments, the powders and coatings produced contain less than 0.1% copper by weight.

[0078] application

[0079] In example embodiments, the alloy is made into a powder. In example embodiments, the alloy is made into a powder by gas atomization. Table 4 below provides measured gas atomized powder chemistries of alloys according to embodiments of the present disclosure. In example embodiments of the present disclosure, the alloy is made into a powder by water atomization.

[0080] Table 4 - Measured Chemistry of Alloys Formed into Powders for Thermal Spraying

[0081] alloy Fe Cr Mo W B C P130-X4 Bal 31.9 10 4.1 5.2 0.08 P130-X5 Bal 41.4 4.5 1.9 4.4 0.05 P130-X7 Bal 40.8 N / A 1.9 4.3 0.06 P130-X9 Bal 40.1 0 2.1 3.7 0.07

[0082] In example embodiments, the alloy may be deposited by high velocity oxygen fuel (HVOF) spraying. In other example embodiments of the present disclosure, the alloy may be deposited by gas fuel HVOF spraying. In further example embodiments of the present disclosure, the alloy may be deposited by liquid fuel HVOF spraying. In still further example embodiments of the present disclosure, the alloy may be deposited by high velocity air fuel (HVAF) spraying. In still further example embodiments of the present disclosure, the alloy may be deposited by plasma spraying. In other example embodiments of the present disclosure, the alloy may be deposited by combustion spraying. In further example embodiments of the present disclosure, the alloy may be deposited by high velocity arc wire spraying. In example embodiments of the present disclosure, the alloy may be deposited by twin wire arc spraying (TWAS). The alloy of the present disclosure may be sintered to form a wear body. The alloy of the present disclosure may be cast to form a wear part.

[0083] The alloys disclosed herein can be used on brake discs and brake drums for passenger cars. The alloys can be used for medium and heavy-duty highway vehicles. The alloys can be used for brake discs in transportation (typically such as trains, street cars, motorcycles, off-highway vehicles, mining trucks).

[0084] The description of the embodiments described herein is intended to provide a general understanding of various embodiments. These descriptions are not intended to be used as a complete description of all the elements and features of the equipment and systems utilizing the structures or methods described herein. After reading this disclosure, many other embodiments will be apparent to those skilled in the art. Other embodiments may be utilized and derived from this disclosure so that structural and logical replacements and changes may be made without departing from the scope of this disclosure. In addition, this disclosure and the accompanying drawings should be considered to be illustrative and not restrictive.

[0085] One or more embodiments of the present disclosure may be referred to herein individually and / or collectively by the term "invention", which is merely for convenience and is not intended to automatically limit the scope of the present application to any particular invention or inventive concept. In addition, although specific embodiments have been illustrated and described herein, it should be understood that any subsequent arrangement designed to achieve the same or similar purpose may replace the specific embodiments shown. The present disclosure is intended to cover any and all subsequent modifications or changes of the various embodiments. After reading this specification, the combination of the above-mentioned embodiments and other embodiments not specifically described herein will be apparent to those skilled in the art.

Claims

1. An iron-based alloy comprising: 20 to 50 wt% Cr; 3 to 6 wt% B; Mo; W; and The balance of iron and impurities; Wherein under substantially balanced solidification conditions, at 1300 K, the pitting resistance equivalent number (PREN) of the matrix phase as defined in equation (1) is greater than 30: PREN=Cr+3.3*(Mo+0.5*W)+16*N (1); Under substantially balanced solidification conditions, at 1000K, the PREN of the matrix phase is greater than 20; wherein under substantially balanced solidification conditions at 1300K, the mole fraction of the hard phase of the alloy is between 40% and 80%; and Wherein under substantially balanced solidification conditions, the liquidus of the alloy is less than 2000K.

2. The alloy of claim 1, comprising between 0.5 and 20 wt. % Mo+W.

3. The alloy of claim 1, wherein under substantially balanced solidification conditions, the concentration of Cr in the matrix phase at 1300K is greater than 15 wt. % and less than 35 wt. % Cr, and the sum of the concentrations of molybdenum and tungsten at 1300K is greater than 2 wt. % and less than 35 wt. %.

4. The alloy of claim 1 wherein the mole fraction of the intermetallic phase is less than 20% at 800K under substantially equilibrium solidification conditions.

5. A method of forming the alloy of claim 1, comprising atomizing the alloy to form a powder, in particular by gas or water atomization.

6. A method of forming a wear and corrosion resistant coating, the method comprising depositing the alloy of claim 1 onto a substrate.

7. The alloy of claim 1, wherein the arc melt microstructure of the alloy comprises between 45 volume % and 80 volume % of the hard phase.

8. The alloy of claim 7, wherein the arc melt microstructure has a PREN greater than 25.

9. The alloy of claim 1, wherein the alloy is deposited by HVOF and has a porosity of less than 3%.

10. The method of claim 6, wherein the substrate is a brake rotor and the method comprises depositing the alloy of claim 1 onto a brake rotor wear surface of the brake rotor.

11. The method of claim 6, wherein the alloy is deposited by liquid fuel HVOF spraying, high velocity air fuel spraying, plasma spraying, combustion spraying, high velocity arc wire spraying, or twin wire arc spraying.

12. The alloy of claim 1, wherein the hard phase comprises at least one of a boride, a carbide, a borocarbide, an oxide, and a nitride.

13. The alloy of claim 1, wherein the concentration of Mo is up to 15 wt. %.

14. The alloy of claim 1, wherein the concentration of W is up to 15 wt. %.

Citation Information

Patent Citations

  • Tough and wear resistant ferrous alloys containing multiple hardphases

    CN107532265A